Photocatalytic Performance Of Fgnpzno Composite For Methylene Blue Degradation Under Uv-Vis Light Irradiation - Mahmud, Rabiatul Aliah (2020)
Wastewater crisis has been worsening and pollution abatement should be taken seriously to reduce the pollutant content in the water stream. Advanced oxidation processes (AOPs) is known to be an effective method to overcome this raised issue and photocatalysis is the best option among all. This is due to the utilization of renewable energy by using semiconductor and at the same time mineralized the harmful pollutant into non-toxic CO2 and H2O. A novel F-GNP/ZnO composites were synthesized via facile one-step solvothermal method, where the oxygen functionalization of GNP and F-GNP/ZnO composites formation were conducted simultaneously. The low-density oxygen-functional groups attached on GNP was shown by Fourier Transform Infrared Spectroscopy (FTIR) and correlated with Raman spectroscopy. The formation of F-GNP/ZnO heterojunction was shown in the X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), High-Resolution Transmission Electron Microscopy (HRTEM), Energy Dispersive X-Ray (EDX), FTIR and Brunauer-Emmett-Teller (BET), that proves on the intimate contact between F-GNP and ZnO n.p. Then, Photoluminescence (PL) and UV-vis Diffuse Reflectance Spectroscopy (UV-vis DRS) has successfully provides the evidence on reducing recombination of electron-hole pairs and wider light absorption compared to ZnO n.p, respectively. In this study, adsorption and photocatalytic activity of MB was studied and obtained 45% F-GNP/ZnO composite as the best GNP content in the composite with adsorption capability and degradation of MB up to 70% and 87%, respectively. In all, MB removal has successfully achieved with 97% by using 45% F-GNP/ZnO composite. Here, the high adsorption capability of the composites was proven by using Brunauer-Emmett-Teller (BET) surface area, where the surface area is directly proportional to the GNP content in the composites. FTIR and Raman analyses have shown a significant result, where the interaction that contributed to the high adsorption was % − % interaction presence between MB molecule and F-GNP due to the low oxygen density in GNP structure. In addition, process parameter studies concluded that the best photocatalytic activity of 45% F-GNP/ZnO composite was achieved using 0.1 g/L catalyst loading in MB with concentration of 10 mg/L and pH 5. Moreover, pseudo-second order for adsorption and pseudo-first order for photocatalytic activity for 45% F-GNP/ZnO composite were revealed from kinetic studies and obtained rate of 0.2250 g/mg.min and 0.034 min-1, respectively. Based on the scavenger test, hydroxyl radical was found to be the most active species that responsible for the degradation of MB.